Strategi Dakwah Wilayatul Hisbah dalam Pelaksanaan Pengawasan Syari’at Islam di Kota Langsa - Ratna Gustina (Tadabbur: Jurnal Peradaban Islam, 2019)
In the city of Langsa, the violation of Islamic sharia qanun (regional bylaws) has shown a declining trend; however, it still accounts for a large proportion. This is a surprising issue since it is believed that the Wilayatul Hisbah (Islamic religious police force) of Langsa has performed its duties and functions properly. To respond to the issue, the study of this thesis formulated several questions, including: what are the da’wah strategies used by the Wilayatul Hisbah in supervising the Islamic sharia in Langsa? and how are the da’wah strategies of the Wilayatul Hisbahin supervising the Islamic sharia against the perspective of manhaj da’wah? The study used field research approach, using qualitative descriptive analysis method. Data were collected by interview and documentation. The results of the study showed that the Wilayatul Hisbah of Langsa employed two types of da’wah strategies: da’wah bi al-lisan (oral da’wah) and da’wah bi al-hal(practical da’wah). Da’wah bi al-lisanincluded speech, Jum’ah sermon, appeal, discussion, and advice/guidance. Da’wah bi al-halinvolved patrol and raid. Further, in the view of the da’wah manhaj, the da’wah strategies used structural and cultural approaches. The structural approaches included (a) the supervision of the Islamic sharia was conducted by an official institution formed by the government, which was the Wilayatul Hisbah, (b) the Wilayatul Hisbah and the Islamic Sharia Office was merged institutionally, (c) the establishment of Islamic sharia supervisors at the village level by the Wilayatul Hisbah and the sharia supervisors by the village officers, and (d) the development of cooperation between the government agencies (e.g. Islamic Sharia Office, Ulama Consultative Assembly, Civil Service Police Unit, Police, Indonesian National Army, Sharia Court, and non-governmental (Islamic) organizations). The cultural approaches involved implementing the strategic da’wah methods and strategies. The da’wah methods of the Wilayatul Hisbah have been in line with the Qur’an chapter An-Nahl verse 125, which describes da’wah bi al-hikmah (wisdom), da’wah bi al-mauidza al-hasanah (good advice), and da’wah al-mujadalah bi al-latihiya ahsan (good dialog).